A systematic review and meta-analysis of the effects of combined aripiprazole on glycolipid metabolism in schizophrenia - Tianbao Wei; Tianbao Wei; Limei Jiang; Limei Jiang; Ruilin Zhang; Hang Su; Zhenjie Sun; Junwei Sun; Junwei Sun (Frontiers in Psychiatry)
BackgroundCurrent research on aripiprazole adjunct therapy suggests potential benefits in improving psychiatric symptoms and metabolic disorders in patients with schizophrenia. However, the evidence remains limited due to the scarcity of research and a lack of detailed analysis on glucose and lipid metabolism indicators. This study aims to systematically review and analyze randomized controlled trials (RCTs) to evaluate the effects of aripiprazole combination therapy on both psychiatric symptoms and glycolipid metabolism.Materials and methodsA systematic search of PubMed, EMBASE, and Web of Science databases was conducted to identify randomized controlled trials (RCTs) investigating the impact of aripiprazole combination therapy on glycolipid metabolism and clinical symptoms.ResultsAdjuvant treatment with aripiprazole reduced blood glucose, triglycerides, total cholesterol, and LDL levels in patients with schizophrenia, but had no significant effect on HDL levels. In addition, the study results showed a significant improvement in metabolic parameters at short-term (≤ 8 weeks) and dosing doses >15 mg. However, aripiprazole adjuvant therapy may lead to worsening of clinical symptoms, so caution is required when using it clinically.ConclusionsAripiprazole adjunct therapy shows potential benefits in improving both psychiatric symptoms and metabolic parameters, but more comprehensive research is needed to solidify these findings, particularly regarding glycolipid metabolism indicators.